Perlindungan Hukum Hak Anak Sebagai Korban - Agus, Azwar (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Children are a gift from God Almighty who have human dignity and self-worth. Article 28B of the Constitution of the Republic of Indonesia states that every child has the right to survival, growth, and development, as well as protection from discrimination and violence. Every child from birth is entitled to the right to live, grow, develop and thrive safely, according to the Constitution of the Republic of Indonesia. The state is responsible for protecting children from discrimination and violence in their life process. Violations of children's rights occur in almost all countries, especially in countries experiencing armed conflict, as well as in developing and developed countries. Violence against children is often associated with visible violence, such as physical and sexual violence. However, psychological and social (structural) violence, in turn, has devastating and lasting consequences for children. The process of economic growth has created social and child problems, such as street children, child labour, sexual exploitation of children, child prostitution, and child trafficking. Child abuse is commonly caused by poverty, which is often associated with mental distress, unemployment, and low levels of education. The rights of children as victims need special attention, because in general, children's rights are often neglected. Concrete and progressive steps need to be taken, including ratifying the International Convention on Children so that it can be implemented comprehensively.